2007
DOI: 10.1186/1475-2875-6-85
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported use of anti-malarial drugs and health facility management of malaria in Ghana

Abstract: Objective: To assess the appropriateness of self-reported use of anti-malarial drugs prior to health facility attendance, and the management of malaria in two health facilities in Ghana.Method: A structured questionnaire was used to collect data from 500 respondents who were diagnosed clinically and/or parasitologically for malaria at Agogo Presbyterian Hospital and Suntreso Polyclinic, both in the Ashanti Region of Ghana. Collected information included previous use of anti-malarial drugs prior to attending th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 12 publications
8
52
0
Order By: Relevance
“…Other sources of unprescribed drugs were what remained from previous illness, from friends/relatives and the shops. These findings are similar to those reported locally in Kenya (Deressa, et al 2003;Buabeng, et al 2007;Aborah, et al 2013). Sourcing medications from what remained in previous illness, friends/relatives and local shops is alarming because these sources indicate possible overdose, under dose, poor adherence to recommended prescription.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Other sources of unprescribed drugs were what remained from previous illness, from friends/relatives and the shops. These findings are similar to those reported locally in Kenya (Deressa, et al 2003;Buabeng, et al 2007;Aborah, et al 2013). Sourcing medications from what remained in previous illness, friends/relatives and local shops is alarming because these sources indicate possible overdose, under dose, poor adherence to recommended prescription.…”
Section: Discussionsupporting
confidence: 81%
“…It has a population of 23 The study targeted the residents of Magwagwa ward in Nyamira County. This population involved adults aged 18-75 years old both male and female.…”
Section: Study Sitementioning
confidence: 99%
“…Each year, between 300 and 500 million new cases are reported worldwide. 4 The global tally of malaria in 2015 was 212 million cases and 4, 29,000 deaths. According to the report fewer than half of the 91 malaria affected countries and territories are on track to achieve the 2020 milestone of a 40% reduction in case incidence and mortility.…”
Section: Malaria Is a Tropical Disease Transmitted By The Female Anopmentioning
confidence: 99%
“…Responses were assigned as 1 = yes/correct and 2 = no/incorrect. Subscale 1 included 2 questions regarding standard treatment regimens for P. vivax (score 2-4) while subscale 2 included 4 questions regarding standard treatment regimens for P. falciparum (score [4][5][6][7][8]. The composite score range was 6-12 and a lower score indicated better knowledge.…”
Section: Study Toolmentioning
confidence: 99%
“…In the case of malaria several studies have reported inappropriate prescribing practices in both public and private health-care facilities due to lack of adherence of prescribers with the STGs [3][4][5][6]. Other studies have reported improved case management after implementation of STGs, but have shown little impact on prescribing habits due to lack of follow up on the implementation of these guidelines [7][8][9]. Rational prescribing requires that prescribers follow a standard process of prescribing in accordance with STGs, which enables a consistent, therapeutically effective and economically efficient use of drugs.…”
Section: Introductionmentioning
confidence: 99%